Sovereign Debt Relief Schemes and Welfare - Husain, Aasim (IMF Working Papers; Working Paper ;, 1992)
This paper shows that concerted debt reduction may be welfare-improving even when the investment disincentive effect of a debt overhang is not large enough to place the debtor country on the wrong side of the debt Laffer curve. Whether the appropriate relief scheme involves debt reduction or new money, however, depends on whether investment disincentives or liquidity constraints dominate. It is shown that, except under very special circumstances, mixed policy packages involving both debt and liquidity relief may not yield the desired results.